Measuring Poverty in the Case of Buenos Aires: Why time deficits matter - Rania Antonopoulos; Valeria Esquivel; Thomas Masterson; Ajit Zacharias (Levy Economics Institute of Bard College, 2016)
We describe the production of estimates of the Levy Institute Measure of Time and Income Poverty (LIMTIP) for Buenos Aires, Argentina, and use it to analyze the incidence of time and income poverty. We find high numbers of hidden poor-those who are not poor according to the official measure but are found to be poor when using our time-adjusted poverty line. Large time deficits for those living just above the official poverty line are the reason for this hidden poverty. Time deficits are unevenly distributed by employment status, family type, and especially gender. Simulations of the impact of full-time employment on those households with nonworking (for pay) adults indicate that reductions in income poverty can be achieved, but at the cost of increased time poverty. Policy interventions that address the lack of both income and time are discussed.
Keywords: C14; C40; D31; J22; 330; Income Poverty; Economic Well-Being; Employment Policy; Fiscal Policy; Gender Disparities; Household Production; Levy Institute Measure of Time and Income Poverty (LIMTIP); Time Deficits; Argentina; Unpaid Work